1998
DOI: 10.1046/j.1523-5394.1998.006006333.x
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Quality of Life in Gynecologic Oncology Patients

Abstract: Health professionals do not generally assess spiritual well-being in their evaluations of patients' needs. The findings from this study support the inclusion of spirituality as part of routine patient assessment and intervention. Clinical intervention that would increase a patient's level of spiritual awareness and his or her level of comfort associated with a personal perspective on death could help decrease the patient's level of psychosocial distress. Despite the medical establishment's bias to the contrary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
66
1
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 20 publications
4
66
1
5
Order By: Relevance
“…Another special population in which religion has been associated with quality of life is cancer patients. 29 Giorella et al 30 found a correlation between levels of spirituality as measured by the Spiritual Well-Being Scale and quality of life as measured by the Functional Living Index: Cancer. In this sample drawn from patients with gynecologic cancer, the effect was particularly strong among older patients.…”
Section: Well-beingmentioning
confidence: 99%
“…Another special population in which religion has been associated with quality of life is cancer patients. 29 Giorella et al 30 found a correlation between levels of spirituality as measured by the Spiritual Well-Being Scale and quality of life as measured by the Functional Living Index: Cancer. In this sample drawn from patients with gynecologic cancer, the effect was particularly strong among older patients.…”
Section: Well-beingmentioning
confidence: 99%
“…Independently of its effect on the evolution of diseases, this dimension has been identified as very relevant and an important domain to be taken into account when evaluating quality of life [11][12][13][14][15][16] . As an example of acknowledging the importance of the spiritual dimension, the World Health Organization, included a domain on spirituality/religiousness/personal beliefs 17 in its instrument for the evaluation of quality of life (WHOQOL) 14 .…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have also shown that religiosity and spirituality significantly contribute to psychosocial adjustment to cancer and its treatments (Musick et al, 1998;Nelson et al, 2002;Weaver & Flannelly, 2004) and to quality of life in cancer patients, even in the face of high levels of symptoms such as pain and fatigue (Gioiella et al, 1998;Brady et al, 1999).…”
Section: Introductionmentioning
confidence: 99%